The Buffalo, Ben, and me - Parnell, Todd, 1947- (University of Missouri Press, 2007)
"A true story of one man's search for meaning in his life and his efforts to motivate his son, blending love of family with love of nature in a tale of transformation. An account of how a trip down a wild river inspired both to a better use of their lives"--Provided by publisher.